Gut Microbial Dysbiosis and Cognitive Impairment in Bipolar Disorder: Current Evidence - Dai, Wenyu; Liu, Jieyu; Qiu, Yan; Teng, Ziwei; Li, Sujuan; Yuan, Hui; Huang, Jing; Xiang, Hui; Tang, Hui; Wang, Bolun; Chen, Jindong; Wu, Haishan (Frontiers in Pharmacology, 2022)
Recent studies have reported that the gut microbiota influences mood and cognitive function through the gut–brain axis, which is involved in the pathophysiology of neurocognitive and mental disorders, including Parkinson's disease, Alzheimer's disease, schizophrenia, and so on. These disorders pathophysiologically overlap with cognitive dysfunction in bipolar disorder (BD), including neuro-inflammation and dysregulation of various neurotransmitters (i.e., serotonin and dopamine). There is also emerging evidence of alterations in the gut microbial composition of patients with BD, suggesting that gut microbial dysbiosis contributes to disease progression as well as the cognitive impairment in BD. Therefore, microbiota-centered treatments may be effective adjuvant therapies for BD-related cognitive impairment. Given that studies focusing on connections between the gut microbiota and BD-related cognitive impairment are lagging behind those on other neurocognitive disorders, this review sought to explore the potential mechanisms of gut microbial dysbiosis to affect cognitive function in BD and to identify potential microbiota-centered treatments.